PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS KEARIFAN LOKAL SUKU SAMAWA PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM SOSIAL DI SEKOLAH DASAR NEGERI 02 MERARAN - Bella Novita Sari; Muhammad Makki; Muhammad Sobri; Siti Istiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop a valid and practical learning module based on the local wisdom of the Samawa tribe in science learning for grade 4 at SDN 2 Meraran. This study is a type of Research and Development (R&D) research using the ADDIE development model. The data collection techniques used were interviews, observations, and questionnaires. The research instruments used were media and material expert validation sheets, teacher and student response questionnaires. Data analysis was carried out qualitatively and quantitatively. The results of the study explain the process of developing a learning module based on the local wisdom of the Samawa tribe in science learning for grade 4 which was carried out through five stages. The first stage of analysis includes needs and curriculum analysis, the second stage of design to determine the concept of the learning module, the third stage of development to realize the learning module product and the validation process was carried out, the fourth stage was implementation which was tested at SDN 2 Meraran, and the fifth stage of evaluation to see and evaluate all stages of development that have been carried out. After the five stages were completed, the learning module based on the local wisdom of the Samawa tribe received a percentage of 89.4% with very valid criteria from media experts, a percentage of 82.1% with very valid criteria from material experts, a percentage of 95% with very practical criteria from teacher responses, a percentage of 97.3% with very practical criteria from student responses in small group trials, a percentage of 94.6% with very practical criteria from student responses in large group trials. Therefore, it can be concluded based on the results of the study that the development of a learning module based on the local wisdom of the Samawa tribe in class IV science learning can be stated as very valid and very practical.